Cluster Preface: Chemical Synthesis and Catalysis in India - Maiti, Debabrata; Mukherjee, Santanu (Synlett, 2023)
Debabrata Maiti (left) received his Ph.D. from Johns Hopkins University in 2008 under the supervision of Prof. Kenneth D. Karlin. After postdoctoral studies at MIT with Prof. Stephen L. Buchwald, he joined the Department of Chemistry at IIT Bombay in 2011. His research interests are focused on the development of new and sustainable synthetic and catalytic methodologies. He is currently an Associate Editor of the Journal of Organic Chemistry.Santanu Mukherjee (right) obtained his Ph.D. in 2006, working under the supervision of Prof. Albrecht Berkessel at the Universität zu Köln, Germany. He subsequently worked as a postdoctoral fellow with Prof. Benjamin List at the Max-Planck Institut für Kohlenforschung, and with Prof. E. J. Corey at Harvard University. In 2010, he joined the Department of Organic Chemistry at IISc Bangalore. His research interests revolve around various aspects of asymmetric catalysis, with particular emphasis on organocatalytic enantioselective desymmetrization and transition-metal-catalyzed enantioselective allylic, allenylic and propargylic substitution reactions. He is an Associate Editor of Organic & Biomolecular Chemistry.